INTERFAITH MARRIAGE AFTER THE ISSUANCE OF SUPREME COURT CIRCULAR LETTER NO. 2 OF 2023 - Annuur Fitria Rahayu (YURIS: Journal of Court and Justice, 2025)
Religious intermarriage in Indonesia has been a complex issue for a long time, due to the absence of explicit provisions regulating it under Law No. 1 of 1974 on Marriage. This research aims to analyze the legal implications of marriage across faith boundaries before and after the enactment of the Supreme Court Circular Letter (SEMA) No. 2 of 2023, which provides guidelines for judges in handling petitions for cross-religious and interbelief marriage registration. Employing a doctrinal (normative juridical) research method, this study examines relevant legal norms contained in statutory regulations, judicial decisions, and scholarly works. The findings reveal that prior to SEMA No. 2 of 2023, district court judges demonstrated inconsistency in granting or rejecting interfaith marriage applications, resulting in legal uncertainty. The issuance of SEMA No. 2 of 2023 clarifies the judicial stance by directing courts to reject such applications, thereby reinforcing that interfaith marriages are not legally valid under Indonesian law. Consequently, interfaith marriages are not registerable in the civil registry system, leading to significant legal consequences, including the absence of legal recognition for the marriage, uncertainty in marital property rights, and the limitation of a child’s civil relationship to the mother. In conclusion, the circular seeks to harmonize legal practice and strengthen the principle of legal certainty in marriage law, although it simultaneously raises debates regarding human rights and religious freedom.